Adsorption kinetics of divalent metals on amino-functionalized carbon nanomaterial - Božo Dalmacija; Aleksandra Šućurović (Zaštita Materijala)
The subject of this study was to investigate the adsorption behavior of selected divalent metals (Cu (II), Cd (II), Pb (II)) on amino-functionalized multiwalled carbon nanotubes, MWCNT-NH2, at four selected pH values (3; 4.5, 6, 11), in order to estimate the possibility of using MWCNT-NH2 to remove ion metal from aqueous solutions at relatively low concentrations (0.01-0.1 mg L-1). The focus of the study was to determine the adsorption mechanism at the experimental conditions. The adsorption of divalent metal ions on MWCNT-NH2 was best described by the pseudo-second order kinetics model, which indicates that adsorption can be attributed to the chemical interactions between the adsorbates and the binding groups on the surface of the adsorbent. Modeling the adsorption rate by the Weber-Morris diffusion model indicated that intra-particle diffusion, although a slower step than external diffusion, is not the only limiting step in the adsorption process, and that the interaction of the investigated ions with the binding sites on the adsorbent surface also control the adsorption rate. Assessment of the impact of pH on the adsorption rate has shown that the pH value, in the investigated range, has the highest effect on the adsorption efficiency of Cu (II) and the lowest for the removal of Cd (II).